Authoritarian practices on the rise? Reflections from a Médecins Sans Frontières research programme on the engagement between international humanitarian non-governmental organisations and states - Cunningham, Andrew; Healy, Sean (Frontiers in Political Science, 2025)
The engagement between international humanitarian non-government organisations (INGOs) and states has long been a contested space. This theme has become more pertinent against the backdrop of a widely perceived global ‘rise in authoritarianism’. This paper presents research by Médecins Sans Frontières (MSF) into factors influencing INGO-state engagement. The research examined the principal factors that influence the attitudes that states take towards international humanitarian NGOs working on their territories during situations of crisis. This paper reviews the findings from four field case studies (Bangladesh, the Kurdistan Region of Iraq, Chad, and Italy) as well as findings from a desk study on the current situation in Afghanistan and a review of MSF’s history with states. The research was grounded in a theoretical framework which integrates the concepts of authoritarian practices (Glasius), regulatory practices, the differentiation between strategic and tactical levels of engagement, and conceptions of legitimacy.